The Factor Structure of The Working Alliance Inventory in Cognitive-Behavioral Therapy - Andrusyna, Tomasz P. (American Psychiatric Press, Inc, 2001)
Studies of the therapeutic alliance in cognitive-behavioral therapy (CBT) have varied in their results, necessitating a deeper understanding of this construct. Through an exploratory factor analysis of the alliance in CBT, as measured by the Working Alliance Inventory (shortened, observer-rated version), the authors found a two-factor structure of alliance that challenges the commonly accepted one general factor of alliance. The results suggest that the relationship between therapist and client (Relationship) may be largely independent of the client's agreement with and confidence in the therapist and CBT (Agreement/ Confidence), necessitating independent measures of these two factors, not one measure of a general alliance factor.